A Study: Positive Psychology and Bhagavad Gita: Exploring the Concepts and Significance of Bhagavad Gita in Positive Psychology (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Individuals have struggled for the comprehensive development of life since ancient times. Atthat time, the Vedas and the Upanishads were deeply ingrained in the lives of the majority of Indians.Similar to how the Bible did, the Gita became well-known not only in India but also throughout the rest ofthe world as a moral and spiritual manual for mankind. Since reason is so important to human existence, itis used to analyse a wide variety of worldly phenomena. So, in order to be satisfied with any doctrine, acritical investigation becomes necessary and more urgent. There is no exception in the Bhagavad Gita.Numerous concepts in the text raise complex issues, and the implicit cosmology, metaphysics,pragmatism, epistemology, and spirituality of the Bhagavad Gita have been the focus of this research. Thepurpose of the current research was to identify the many concepts that the Bhagavad Gita outlines whilealso critically analysing those concepts to shed light on them. In this article, the significance of the Gitahas been addressed in relation to a particular area of positive psychology.Some academics believe thatthe work has an allegorical significance and has no historical basis, but others believe that the eventsdescribed in the Gita actually happened as they are described. This study offers a critical examination ofthis topic in light of many commentators' points of view.